2021
DOI: 10.3390/vaccines9101052
|View full text |Cite
|
Sign up to set email alerts
|

Shooting at a Moving Target—Effectiveness and Emerging Challenges for SARS-CoV-2 Vaccine Development

Abstract: Since late 2019 the newly emerged pandemic SARS-CoV-2, the causative agent of COVID‑19, has hit the world with recurring waves of infections necessitating the global implementation of non-pharmaceutical interventions, including strict social distancing rules, the wearing of masks and the isolation of infected individuals in order to restrict virus transmissions and prevent the breakdown of our healthcare systems. These measures are not only challenging on an economic level but also have a strong impact on soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 197 publications
(255 reference statements)
0
24
0
Order By: Relevance
“…A variety of SARS-CoV-2 vaccines are currently being developed and some have been approved, including inactivated-, subunit-, vector-, mRNA-, and DNA vaccines ( 13 , 14 ). Although several vaccines against COVID-19 are promising, developing more effective and cross-protective vaccines is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of SARS-CoV-2 vaccines are currently being developed and some have been approved, including inactivated-, subunit-, vector-, mRNA-, and DNA vaccines ( 13 , 14 ). Although several vaccines against COVID-19 are promising, developing more effective and cross-protective vaccines is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…415 , 416 Between December 28, 2020, and May 10, 2021, 256,037 people in Qatar received at least one dose of the mRNA-1273 vaccine, whereas 181,034 people received two doses. Real-world data showed that effectiveness of mRNA-1273 against Alpha and Beta variants was 100% and 96.4%, respectively, 417 , 418 whereas effectiveness against Delta was slightly lower (73.1%). 102 Other studies have shown that mRNA-1273 is still quite effective in congregate settings or higher-risk exposure such as prisons or hospitals in which the Delta variant was prevalent.…”
Section: Progress In Clinical Research On Mrna Vaccinesmentioning
confidence: 99%
“…Initially, Sputnik V has faced lots of criticism for unseemly haste with low transparency, but the outcome and interim analysis reports published in the Lancet have attempted to do away with the allegations of non-transparency [ 84 , 86 , 87 , 88 , 89 , 90 ]. The Gamaleya Research Institute (Moscow, Russia) claimed that Sputnik V is more than 90% effective against the B.1.617.2 variant of CoV [ 91 ].…”
Section: Vaccines Approved For Public Usementioning
confidence: 99%